Identification of a precursor of 2-mercapto-3-methyl-1-butanol in beer. (30th July 2018) - Noba, Shigekuni; Yako, Nana; Sakai, Hiroaki; Kobayashi, Minoru; Watanabe, Tetsuya
Highlights: The precursor of 2-mercapto-3-methyl-1-butanol (2M3MB) was purified from hop extract. The main precursor of 2M3MB was identified as 2, 3-epoxy-3-methylbutanal. 2, 3-Epoxy-3-methylbutanal was detected for the first time in food. The conversion rate of this precursor to 2M3MB is approximately 3%. Abstract: 2-Mercapto-3-methyl-1-butanol (2M3MB) imparts an onion-like off-flavor to beer and is believed to result from the hot aeration of brewer's wort. However, little has been reported regarding the mechanism of formation of 2M3MB. This paper investigates the precursors of 2M3MB formed during the brewing process. Our study of a cysteine conjugate as a precursor showed its negligible contribution to the formation of 2M3MB. The 2M3MB precursor was found to be a volatile compound because 2M3MB was formed in the distillate of hop extract. The precursor was purified through distillation, column chromatography, and preparative gas chromatography, and the 2M3MB-producing potential was measured as an index for estimating the concentration of the precursor. The accurate mass of the precursor was measured using gas chromatography coupled to quadrupole-time-of-flight-mass spectrometry (GC/QTOF). The molecular structure was identified from the product ion spectra by GC/QTOF to be 2, 3-epoxy-3-methylbutanal.